PENGARUH PROGRAM KELUARGA HARAPAN (PKH) TERHADAP PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI KABUPATEN PIDIE. - Rusydi, Abubakar Hamzah, Sofyan Syahnur. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2015)
Abstract: The purpose of this study was to determine the influence of the Family Hope Program (PKH) for Improving the Quality of Human Resources in Pidie district. The sample in this study were selected very poor households that receive assistance Indrajaya Sub District, Mutiara Timur Sub District and Pidie Sub district. Sampling was done randomly by using the